TORTOR PARSAORAN PADA UPACARA ADAT PERNIKAHAN PARMALIM PADA MASYARAKAT BATAK TOBA DI DESA MARIAH JAMBI KECAMATAN JAWA MARAJA BAH JAMBI TIMURAN KABUPATEN SIMALUNGUN - RIRIS GETHA MUNTHE (Gesture: Jurnal Seni Tari, 2014)
This study aims to determine how the meaning of the symbols on Tortor Parsaoran in Toba Batak society, the structure of the motion contained in Tortor Parsaoran and form of presentation Tortor Parsaoran in Toba Batak society. In the discussion of this writing, used theories of writing-related topics, such as the theory of meaning, symbols theory, the theory of the structure, tortor sense and understanding of traditional ceremonies. The method used is descriptive qualitative. To complete the data in this study, researchers conducted field observations, videos, interviews and documentation. The population in this study is the Toba Batak society who are in Simalungun District of Java Maraja Bah Jambi easterlies, artists and local traditional leaders. The results based on the data collected can be seen that the Toba Batak tribe in ancient times Ugamo Malim embrace trust as a belief system that existed since the ancestors of the Toba Batak society. People who fall into Ugamo called Parugamo Malim Malim (Malim Ugamo followers) or commonly abbreviated with Parmalim said. Tortor Parsaoran in cult ugamo malim (Parmalim) in Toba Batak society means brotherhood, fellowship among communities, range of motion tortor little and goes into a loop. Range of motion consists of six movements of hohom, mangurdot Somba, mangurdot manea, mangurdot mangorai, mangurdot manghorus, Embas, which each movement has a symbolic meaning motion. Tortor structure on Parmalim wedding ceremonies, some of them 1.Tortor initially conducted by the hasuhuton (the organizer of the party), semarga relatives and the bride and groom. 2.Tortor Somba carried by the bride homage to hula, bones and all guests. 3.Tortor mangaliat hula performed by giving thanks to Boru 4.Tortor hasahatan / sitio-tio performed by groups of elders in the village. 5.Tortor Parsaoran done by all the family party. Tortor Parsaoran in the implementation or presentation on Parmalim wedding ceremonies is danced by the whole family arrangements for the party. While the musical accompaniment in the form of gondang Idang tortor-Idang, where gondang the role of tortor which is a musical accompaniment. Keywords: Tortor Parsaoran.